Pemblokiran Sertifikat Tanah Sebagai Bentuk Wanprestasi Jual Beli Tanah (Studi Kasus terhadap Putusan Nomor 1530 K/Pdt.G/2003) - Syakuran, Khaidar Abdan; Pitaloka, Putri Galuh; Hadi, Rival Mahesa Fauzan; Yuliandra, Stefie; Syakirah, Davina; Andira, Ilham; Rusdiananto, Gavra Fiko; Syaihputra, Brian Maulana Muhammad; Haryadi, Raina Ardelia; Sapitri, Irena; Lagut, Veronica Sekar Wela; Rizkianti, Wardani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Buying and selling is a process of exchanging goods or assets based on an agreement, as regulated under Article 1320 of the Indonesian Civil Code (KUHPerdata). However, the implementation of such transactions often faces challenges due to breaches of agreement, leading to disputes, as exemplified in Decision No. 1530 K/Pdt/2003. This article aims to analyze the resolution of land sale and purchase disputes when one party fails to fulfill the agreement and examine the impact of the sale and purchase deed (AJB) as evidence in disputes that result in the blocking of land certificates. The study also seeks to provide insights into the importance of strengthening regulations and dispute resolution mechanisms in land sale and purchase transactions to ensure legal certainty and protect the rights of the parties involved.